Perceptions of mental illness in a Bangladesh village - Selim, Nasima; Satalkar, Priya (BRAC University, 2010)
In this paper, we discuss the perceptions of people from a Bangladeshi village about what they considered to be 'mental illness'. Observations, informal conversations, interviews, focus group discussions, and illness narratives include the perspectives of both the caregivers and the patients in Kakabo. The villagers provided us with local terms (e.g., paglami), their beliefs about illness causation, treatment, and its effects. Some illnesses were believed to be present from birth and mostly incurable. Supernatural causation and local cure were mentioned for some other categories of illness. There were very few instances when they accessed the existing mental health care in the big city. Widespread abuse of various substances was reported. In general, the participants showed broader acceptance of these conditions, excepting certain forms of substance abuse. We discus these findings in relation to defining their perceptions in terms of explanatory model(s). Our analysis is also concerned with the way people 'embody' their 'illness experience', and how this is made relevant for the process of coping with 'mental illness' in the family. Further investigation, however, is required to clarify some of the questions and ambiguities arising from this small-scale exploratory qualitative study.